Analysis of Oil-Gas Two-Phase Flow and Parameter Influence of Star Herringbone Gearboxes Based on the SPH Method - Wang Lin; Du Zekai; Zheng Zhizhen; Wang Yong (Jixie chuandong)
The flow field distribution in the star herringbone gearbox lubricated by oil injection is very complex, and there are many difficulties in the flow simulation analysis. Based on the smooth particle hydrodynamics (SPH) method, the particle simulation model of the flow field in the star herringbone gearbox with oil injection lubrication is established, and the oil-gas two-phase distribution characteristics at different cross-section positions in the gearbox are obtained. The oil-liquid distribution and velocity distribution of flow field under different gear speeds and oil injection speeds are compared and analyzed. The results show that the oil flow field distribution is obviously different at different cross-section positions in the gear shaft direction, the oil flow in the middle cross-section position of the gearbox is the largest, and the local eddy current phenomenon occurs in the area between the solar wheel, planetary wheel and oil injection port. The gear speed and oil injection speed have great influence on the oil distribution in the gearbox.